2022
DOI: 10.1002/cre2.665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the shear bond strength and remineralization effect of calcium silicate‐based and conventional self‐adhesive resin cements to caries‐affected dentin

Abstract: Objective Given the importance of preserving caries‐affected dentin (CAD) in conservative dentistry, the shear bond strength (SBS) of different resin cements to CAD has been investigated. Here, we aimed to compare the SBS and remineralizing effect of a calcium silicate (TheraCem) and conventional self‐adhesive cement (Panavia SA) on the SBS of CAD. Materials and Methods Forty‐eight extracted third molars (24 sound and 24 CAD) were used. In each group, 12 teeth were prepared for bonding to TheraCem or Panavia S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…TheraCem (Bisco) is a commercial calcium silicate cement that can release fluoride and calcium ions. Studies by Tavangar et al [119] showed that TheraCem has better shear bond strength (SBS) when bonded to caries-affected dentin as compared to conventional self-adhesive cement (Panavia SA). It has been established that excellent bonding properties depend on micromechanical interlocking and chemical adhesion between the adhesive and dentin [120].…”
Section: Effect Of Calcium Silicate Fillers On the Remineralization A...mentioning
confidence: 99%
“…TheraCem (Bisco) is a commercial calcium silicate cement that can release fluoride and calcium ions. Studies by Tavangar et al [119] showed that TheraCem has better shear bond strength (SBS) when bonded to caries-affected dentin as compared to conventional self-adhesive cement (Panavia SA). It has been established that excellent bonding properties depend on micromechanical interlocking and chemical adhesion between the adhesive and dentin [120].…”
Section: Effect Of Calcium Silicate Fillers On the Remineralization A...mentioning
confidence: 99%
“…Calcium silicate resin demonstrates superior shear bond strength compared to traditional self-adhesive resins, effectively sealing dentin tubules [101]. When enhanced with calcium and phosphate ions, adhesive resins can function as ionic reserves, fostering the remineralization of tooth surfaces.…”
Section: Resin-based Materialsmentioning
confidence: 99%